Analysis of eight magnetic chemically peculiar stars with rotational modulation. Issue 4 (30th September 2022) - Kobzar, O; Khalack, V; Bohlender, D; Mathys, G; Shultz, M E; Bowman, D M; Paunzen, E; Lovekin, C; David-Uraz, A; Sikora, J; Lampens, P; Richard, O
ABSTRACT: Since the end of 2018, the Transiting Exoplanet Survey Satellite ( TESS ) has provided stellar photometry to the astronomical community. We have used TESS data to study rotational modulation in the light curves of a sample of chemically peculiar stars with measured large-scale magnetic fields (mCP stars). In general, mCP stars show inhomogeneous distributions of elements in their atmospheres that lead to spectroscopic (line profile) and photometric (light curve) variations commensurate with the rotational period. We analyzed the available TESS data from 50 sectors for eight targets after post-processing them in order to minimize systematic instrumental trends. Analysis of the light curves allowed us to determine rotational periods for all eight of our targets. For each star, we provide a phase diagram calculated using the derived period from the light curves and from the available measurements of the disc-averaged longitudinal magnetic field 〈 B z 〉. In most cases, the phased light curve and 〈 B z 〉 measurements show consistent variability. Using our rotation periods, and global stellar parameters derived from fitting Balmer line profiles, and from Geneva and Strömgren–Crawford photometry, we determined the equatorial rotational velocities and calculated the respective critical rotational fractions v eq / v crit . We have shown from our sample that the critical rotational fraction decreases with stellar age, at a rate consistent with the magnetic braking observed in the larger population of mCP stars.